Prosopographic research in library science: a methodological aspect - G. V. Varganova (Библиосфера, 2015)
Prosopographic research is a kind of research used by specialists in different spheres of scientific knowledge including library science. It is applied to study historical issues in a wide range of problems of library science and librarianship development, which are relevant to modern period. Prosopographic research main stages are represented related to compiling a collective biography of a group of persons; advantages and limitations of a prosopographic method are analyzed, it is defined as a cross-disciplinary one. Main problems to be solved in this study course are determined: collection, analysis, assessment of representativeness and reliability of material to be studied for identifying similar and unique information, criteria formulation for selecting the members of the study group, drafting a questionary, procedures of research results analysis and interpretation. «Library Encyclopedia» and reference books issued by the Russian National Library, the Library of the Russian Academy of Sciences and the State Public Scientific-Technological Library are recommended as sources for prosopographic research. The necessity of a prosopographic database generation is proved